Moral Elevation and Moral Beauty: A Review of the Empirical Literature. Issue 4 (December 2016) - Pohling, Rico; Diessner, Rhett
Moral elevation is defined as the emotional response to witnessing acts of moral beauty. Studies have found that elevation entails pleasant feelings of warmth in the chest, feeling uplifted, moved, and optimistic about humanity. Elevation motivates affiliation with others as well as moral action tendencies. The main goal of this review was to gather and organize the empirical findings from the last 16 years of elevation research with regard to psychological and physiological characteristics, motivational tendencies, behavioral outcomes, neuronal mechanisms, moderators, and correlates of elevation. A secondary goal was to examine whether elevation is congruent withFredrickson's (2001) broaden-and-build theory of positive emotions. It was concluded that there is strong evidence that elevation broadens the thought-action repertoire and relatively weak evidence that it builds lasting resources. Potential evolutionary functions, the forms of measurement of elevation, the process of how elevation is triggered, practical applications and directions for future research were also addressed.